An Insight into Skincare and Antiaging Products Derived from Marine Origin - Singh, Amit Kumar; Kumar, Pankaj; Vamsi Kumar, Attuluri; Garg, Vivek Kumar; Kaur, Jappreet; Buttar, Harpal Singh; Yadav, Vikas (Scripta Medica, 2026)
Marine resources are attracting significant attention from the cosmetics sector as a source of active ingredients. The oligo-elements like iron, copper and zinc, as well as proteins, amino acids, carbohydrates and vitamins A, B and C, are abundant in both micro- and macro-algae. These active components provide a range of benefits including hydration, firmness, shine, protection and slimming effects. Marine life is found in a variety of environments, each offering unique compounds with beneficial properties. Organisms living in places with high UV radiation levels, like tropical regions or shallow seas, can create compounds that provide photoprotection. Similarly, microbes that thrive in extreme conditions, such as hydrothermal vents, can produce substances with antioxidant properties. Polysaccharides from marine algae, such as alginate and carrageenan have been developed as cosmetics owing to their moisturising and skin-barrier enhancing properties. The scientific community believe that harnessing the potential of marine bioactive compounds is highly beneficial as medicinal products. By exploiting these resources, the skincare industry can develop innovative medicinal products that promote healthy, youthful skin while supporting environmental sustainability. In the present review, we have discussed the compounds derived from marine sources and their skin-nourishing properties marine-derived compounds, emphasising their role in developing novel skincare and antiaging products.